Environmental Governance and Green Energy: An Administrative Toolkit to Reduce Environmental Degradation - Muhammad Sajjad Hussain; Muhammad Atif Nawaz; Tusawar Iftikhar Ahmad; Muhammad Azhar Bhatti (iRASD Journal of Management)
For the last two decades, environmental degradation has become the most serious concern at multiple levels and has gained special attention of literature and policymakers. Strict implementation of the evidence-based policy solutions could serve as a regulatory tool to gradually overcome this issue. The current study examines the role of environmental governance (environmental-related taxes) and green energy (renewable energy consumption and production) on the carbon dioxide (CO2) emission of the ten most CO2 emitting countries. The study has used economic growth as the control variable. Data has been extracted from the world development indicators (WDI) from 2012 to 2020. The study employed the robust standard error and fixed effect model (FEM) to examine the linkage among the variables under consideration. The results indicated that environmental governance and green energy have a significant role in reducing environmental degradation in the ten most CO2 emitting countries in the world. The findings of this empirical and evidence-based study suggest to the relevant environmental management authorities, administrative bodies, and policymakers to incorporate environmental governance and green energy in their environmental management strategies.